Acute Flaccid Paralysis by Enterovirus D68 Infection: First Italian Description in Adult Patient and Role of Electrophysiology - Ceccanti, Marco; Sbardella, Emilia; Letteri, Federica; De Michele, Manuela; Falcou, Anne; Romanzi, Federica; Onesti, Emanuela; Inghilleri, Maurizio (Frontiers in Neurology, 2017)
A Peruvian woman was admitted to the Emergency Department, due to an acute flaccid paralysis (AFP) of the upper limbs that progressively involved also lower limbs and respiratory muscles. She previously suffered from non-Hodgkin’s lymphoma and had to undergo hematopoietic stem cell transplantation. A magnetic resonance imaging showed a T2 hyperintensity in the anterior and central region of the cervical segment with an elective involvement of gray matter. This finding, combined with other clinical, laboratory, and electrophysiological data, led to a diagnosis of AFP. Enterovirus D68 was isolated in the patient’s cerebrospinal fluid, plasma, and throat swab. To our knowledge, this is the first Italian case of AFP by Enterovirus D68 infection in an adult. The diagnostic assessment and management of AFP by Enterovirus D68 are discussed.